Storytelling for Systems Change: insights from the field - Snow, Thea; Murikumthara, David; Dusseldorp, Teya; Fyfe, Rachel; Wolff, Lila; McCracken, Jane (Centre for Public Impact, 2022)
Capturing the impact of community-led work The Centre for Public Impac t, Dusseldorp Forum, and Hands Up Mallee have been exploring how stori es can be used to more effectively communicate the impact of community -led systems change work. Community-led place based initiatives are mo delling new ways of working - shifting away from top down, program-foc ussed approaches towards an approach grounded in systems thinking and community-led innovations. However, while these stories of change are sitting in communities, they’re often not being told or celebrated. We wanted to understand why this is, and what might be done to better en able these stories to be shared and heard. The story of storytelling W e talked to a range of people to uncover the story of storytelling - i ncluding collective impact backbone team members, community members, s torytelling experts, and those working in and around community-led sys tems change initiatives across Australia. We explored the roles storie s play in different communities; what good storytelling looks like; wh at barriers to storytelling might be; and what role stories can play i n supporting systems change. Our findings We have learned through this project that stories can be used both to change the system and to eva luate, understand and showcase the change that is occurring in communi ties. We have heard that different stories require different approache s – stories that are seeking to enable change look different to those that are seeking to celebrate change.